Impact of Poverty, Economic Growth, and Information and Communication Technology on Human Development - Siti Komariyah; Teguh Hadi Priyono; Clarissa Ardella Nathania (Journal of Economics, Business, and Accountancy Ventura, 2023)
Human development is one of the main problems in developing countries, as seen from the relatively low Human Development Index (HDI) level. This study examines how poverty, economic growth, and information and communication technology (ICT) influenced the quality of human development in Indonesia in 2014–2020. The research method used was panel data regression analysis with cross-sectional observations of 34 provinces. The study results show that poverty has a negative and significant impact on the quality of human development in Indonesia. Meanwhile, ICT has a positive and significant impact on the quality of human development. There is no significant evidence of the effect of economic growth on the quality of human development. The results of this study are helpful for the central and regional governments in making policies related to human development in Indonesia. This finding implies that coordination of poverty reduction efforts between central and local governments is essential for human development. In addition, the government needs to pay attention to the quality of the distribution of ICT availability between regions to improve the quality of human development in Indonesia.